Experiencias de vida en mujeres con trastornos de la conducta alimentaria y su salud bucal (2023)
Eating disorders are a group of diseases and psychological problems recognized for their severity and the effects they can cause in the individual who suffers from them. These tend to have an impact on the quality of life, and in turn, on oral health.Objective: Describe the life experiences of women with eating disorders and oral health